Implementation of a food safety management system in a line of instant drinks (Agroindustria, Sociedad y Ambiente, 2023)
Under the guidelines of the ISO 22000:2018 Standard, a food safety management system was implemented in a cereal-based instant beverage production line, under the following stages Phase I: Definition of the strategic concept of the company Cereales venezolanos y its safety policy, Phase II: Diagnosis of the current situation of the company, Phase III: Formulation of strategies to adapt the line of instant drinks to what is established in the ISO 22000:2018 standard, Phase IV: Implementation of the safety management system food safety designed, in a pilot area. The results obtained showed that the strategic concept of the company and its safety policy are aligned on the premise of developing safe foods with high nutritional value, the food safety management system in the diagnosis made regarding compliance with the ISO standard. 22000:2018 for sections 4 clause 4.3, section 7 clause 7.5 and section 8 clause 8.5 presented a compliance percentage of 42.80% after the implementation of the safety management system in a pilot area, it was obtained that the system was effective upon completion of its implementation by 94.32%. The control of process variables, productivity, communication with interested parties, quality and safety of the finished product and the registration and control of documentation increased.
Keywords: safety, instant drinks, management system.